Female Education and Risk Factors of Noncommunicable Diseases across India: An Exploration - Phadte, Manisha; Rath, Seema (Indian Journal of Pharmacy Practice)
Introduction: Non-communicable diseases are rapidly rising worldwide, causing serious public health concerns that must be addressed. Past studies exhibit the relation between education and the prevalence of non-communicable diseases and the associated risk factors. Therefore, this study aimed to investigate the influence of female education on risk factors such as overweight/ obesity, increased blood sugar, elevated blood pressure, tobacco and alcohol use linked to the incidence of non-communicable diseases across 28 states of India by using the data from National Family Health Survey 5. Materials and Methods: The present study uses National Family Health Survey 5 (2019-21) data. Different groups of female education and various risk factors resulting in non-communicable diseases have been considered to analyse their association. Results: Linear regression analysis revealed a statistically significant association between female education and the risk factors for non-communicable diseases except for alcohol consumption. Conclusion: Education is linked to overweight/obesity, increased blood sugar and elevated blood pressure among females. Therefore, effective awareness programs and promotional activities along with improvement in female education need to be undertaken to help women self-manage risk factors causing non-communicable diseases.
Keywords: Female; Education; Risk Factors; Non-communicable Diseases; India